Abiy’s legitimacy crisis and the Northern armed conflict: re-establish the base or coerce legitimacy? - Abyssinia Abay Mengistu (Cogent Social Sciences, 2024)
This paper investigates Abiy’s legitimacy crisis and resolution of his legitimacy on the way to the Northern Armed Conflict. It is claimed that Abiy lost popularity shortly after his premiership but managed to mobilize people against the Northern Armed Conflict. However, empirical support for this argument has been ambiguous at best. The researcher employed qualitative methods with a case study design. Key informant interviews and secondary sources of data have been used. The northern armed conflict of Ethiopia was crafted by leaders as a disguise for economic underperformance and loss of legitimacy. This paper posits that a leader either recalibrates its base or uses coercion to retrieve legitimacy, but it was found that Abiy did not reestablish the base to retrieve his legitimacy, nor did he utilize coerce. Thus, the paper calls up on a new perspective to legitimacy resolution and shows how intractable ancient hatreds, territorial claims, and self-administration are used for the retrieval.